Geographical Representativeness of Published and Ongoing Randomized Controlled Trials. The Example of: Tobacco Consumption and HIV Infection - Ahmad, Nizar (Public Library of Science, 2011)
BACKGROUND: The challenge for evidence-based healthcare is to reduce mortality and the burden of diseases. This study aimed to compare where research is conducted to where research is needed for 2 public health priorities: tobacco consumption and HIV infection. METHODS: We identified randomized controlled trials (RCTs) included in Cochrane systematic reviews published between 1997 and 2007 and registered ongoing RCTs identified in January 2009 through the World Health Organization's International Clinical Trials Registry Platform (WHO-ICTRP) evaluating interventions aimed at reducing or stopping tobacco use and treating or preventing HIV infection. We used the WHO and World Bank reports to classify the countries by income level, as well as map the global burden of disease and mortality attributable to tobacco use and HIV infection to the countries where the trials performed. RESULTS: We evaluated 740 RCTs included in systematic reviews and 346 ongoing RCTs. For tobacco use, 4% of RCTs included in systematic reviews and 2% of ongoing trials were performed in low- and middle-income countries, even though these countries represented 70% of the mortality related to tobacco use. For HIV infection, 31% of RCTs included in systematic reviews and 33% of ongoing trials were performed in low- and middle-income countries, even though these countries represented 99% of the mortality related to HIV infection. CONCLUSIONS: Our results highlight an important underrepresentation of low- and middle-income countries in currently available evidence (RCTs included in systematic reviews) and awaiting evidence (registered ongoing RCTs) for reducing or stopping tobacco use and treating or preventing HIV infection.